2022
DOI: 10.1002/adsc.202200347
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Intermolecular Asymmetric Allylic Amination with Pyridones

Abstract: We report herein a catalytic synthetic method for enantioenriched N‐substituted pyridones. By employing chiral iridium catalyst generated from the Carreira [P/olefin] ligand, intermolecular asymmetric allylic amination of allyl alcohols with pyridones proceeded smoothly with excellent chemo‐, regio‐ and enantioselectivities (>19:1 N/O, >19:1 b/l and ≥89% ee). The reaction was a kinetic resolution process under mild conditions and displayed a broad substrate scope for both pyridones and allylic alcohols. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…[32] Recently, You's group employed an iridium-catalyzed Nallylation of 2-hydroxypyridines reaction in the kinetic resolution of branched allyl alcohols (Scheme 13). [33] Using [Ir(cod)Cl] 2 / Carreira ligand L6 as catalyst and Zn(OTf) 2 as additive, this kinetic resolution reaction occurred smoothly. The desired αchiral N-allylic pyridones 52 were delivered with up to 42 % yield and 99 % ee, while highly enantioenriched allylic alcohols (R)-51 were recovered.…”
Section: N-allylation Of 2-hydroxypyridinesmentioning
confidence: 93%
“…[32] Recently, You's group employed an iridium-catalyzed Nallylation of 2-hydroxypyridines reaction in the kinetic resolution of branched allyl alcohols (Scheme 13). [33] Using [Ir(cod)Cl] 2 / Carreira ligand L6 as catalyst and Zn(OTf) 2 as additive, this kinetic resolution reaction occurred smoothly. The desired αchiral N-allylic pyridones 52 were delivered with up to 42 % yield and 99 % ee, while highly enantioenriched allylic alcohols (R)-51 were recovered.…”
Section: N-allylation Of 2-hydroxypyridinesmentioning
confidence: 93%
“…An analogous iridium-catalyzed intermolecular asymmetric allylic amination was developed for 4- and 2-hydroxypyridines 1 with allylic alcohols 335 to render N -allylated 2-pyridones and 4-pyridones 337 in good yields with excellent enantioselectivities ( Scheme 159 ). 228 Mechanistic studies indicated that the reaction was a kinetic resolution process and it displayed a broad substrate scope for both pyridines and allylic alcohols. Moreover, the reaction was successfully performed on a gram-scale and the amination product was further derivatized to prove the practicality of this method.…”
Section: Addition Of Other Nucleophilesmentioning
confidence: 99%
“…The catalyst system was made by an iridium complex with Carreira's [P/olefin] ligand L12 with the necessary inclusion of a Lewis acid such as Zn(OTf)2. The reaction obtained the corresponding allylated pyridines of type 98 with excellent chemo-, regio-and enantioselectivities (>19:1 N/O, >19/1 branch/linear and ≥89% ee) (Scheme 32) [78]. Scheme 32.…”
Section: Scheme 24 Palladium-catalyzed Asymmetric Allylation Of 2-hyd...mentioning
confidence: 99%